2022
DOI: 10.1002/mp.15835
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐based radiomics nomogram for the preoperative prediction of deep myometrial invasion of FIGO stage I endometrial carcinoma

Abstract: Background Endometrial carcinoma (EC) is one of the most common gynecological malignancies with an increasing incidence, and an accurate preoperative diagnosis of deep myometrial invasion (DMI) is crucial for personalized treatment. Objective To determine the predictive value of a magnetic resonance imaging (MRI)‐based radiomics nomogram for the presence of DMI in the International Federation of Gynecology and Obstetrics (FIGO) stage I EC. Methods We retrospectively collected 163 patients with pathologically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The FIGO stage is a more widely used and authoritative staging system; according to stage III of the disease, the tumor has invaded the uterine serosal layer or fallopian tubes. For these patients, the rate of postoperative recurrence and distant metastasis is high, even with aggressive surgical treatment, ultimately worsening the patient’s prognosis ( 13 , 14 ). When the tumor thrombus enters the blood or lymphatic vessels, vascular tumor thrombus may lead to lymph node metastasis and, also, distant metastasis ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FIGO stage is a more widely used and authoritative staging system; according to stage III of the disease, the tumor has invaded the uterine serosal layer or fallopian tubes. For these patients, the rate of postoperative recurrence and distant metastasis is high, even with aggressive surgical treatment, ultimately worsening the patient’s prognosis ( 13 , 14 ). When the tumor thrombus enters the blood or lymphatic vessels, vascular tumor thrombus may lead to lymph node metastasis and, also, distant metastasis ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we also established a nomogram prediction model to more intuitively identify the high risk group of tumor-specific death in patients with EC 5 years after surgery and found that the predictive model was reliable. Nomogram predictive models can accurately identify the high risk group of poor prognosis in a variety of diseases ( 13 , 19 - 22 ). Some authors have discussed on the role of nomogram predictive models in evaluating patients with EC and found that predictive models have good evaluation value ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present findings, MRS, histological type, LNM and tumor grade were independent factors, and these factors were used to build the model. To the best of our knowledge, there only a few predictive models have been constructed to evaluate MI before surgery, and they are mostly based on MRI radiomics (7,17). The aforementioned studies used parameters such as axial T1-weighted images (T1WIs), T2WIs and diffusion weighted imaging to sketch region of interest, and further least absolute shrinkage and selection operator regression was conducted to narrow the range.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral alveolar echinococcosis is a rare parasitic disease, but it is still a severe public health issue in many parts of the world. We believe that radiomics-based machine learning is a novel tool to investigate this disease, which have been proved as a powerful approach in other fields [ 38 41 ].…”
Section: Discussionmentioning
confidence: 99%